EXCESSIVE TAX CHARGE AND EFFECTS ON DAY-TO-DAY - Imbeloni Mattos, Thulio; Henrique Medeiros de Souza, Carlos; Moraes Marques, Bruna; Machado de Oliveira, Fabio; da Silva Monteiro, Maressa (LINKSCIENCEPLACE, 2026)
It is the knowledge of citizens that the excess of the level of tax enforcement inhibits economic growth: causes suppression of production units; prevents the expansion of the industrial park; decreases the entry of foreign productive capital; increases the number of evaders and defaulters. The Brazil carries the stigma of owning the most expensive tax system and complex world. It’s expensive because of the amount of taxes and regulations that govern it. With the gradual evolution of public expenditure, to meet the diverse needs collective, became indispensable to the State resort to a regular and permanent source of funding, acting through a coercive force to the partial removal of the wealth of individuals, without any consideration. Thus, the tax became the main source of public income needed to finance government activities. Nowadays tax revenue of almost all countries must first be approved by the representatives of the people. The tribute began to form themselves into a disciplined legal category by law and can only be requested by a legal relationship between the state and the subject-taxpayer. The aim of this study contribute to the foundation and awareness of Brazilian citizens to know their rights and duties, as a taxpayer, displaying greater transparency and respect in their dealings with the IRS. Society must be informed of their rights in order to ensure good relations with tax authorities. The study is justified because it is the tax issue is in a key to the development of a nation element, mainly because to meet the public expenditure the state does not have many mechanisms.